Cough as an adverse effect on inhalation pharmaceutical products. (7th August 2020) - Chang, Rachel Yoon Kyung; Kwok, Philip Chi Lip; Ghassabian, Sussan; Brannan, John D.; Koskela, Heikki O.; Chan, Hak‐Kim
Abstract : Cough is an adverse effect that may hinder the delivery of drugs into the lungs. Chemical or mechanical stimulants activate the transient receptor potential in some airway afferent nerves (C‐fibres or A‐fibres) to trigger cough. Types of inhaler device and drug, dose, excipients and formulation characteristics, including pH, tonicity, aerosol output and particle size may trigger cough by stimulating the cough receptors. Release of inflammatory mediators may increase the sensitivity of the cough receptors to stimulants. The cough‐provoking effect of aerosols is enhanced by bronchoconstriction in diseased airways and reduces drug deposition in the target pulmonary regions. In this article, we review the factors by which inhalation products may cause cough.